PENINGKATAN DAYA SAING UMKM HERBAL MELALUI INOVASI PRODUK DAN PEMASARAN DIGITAL DI GAYO LUES (STUDI PEMBERDAYAAN DENGAN MODEL ABCD) - chandra, Riny; Ardiyanti, Dyah Ayu (Universitas Mataram, 2025)
This PKM is highly urgent given the great potential of Gayo Lues Regency in developing herbal products, which has not yet been optimally utilized. The region is rich in economically valuable herbal raw materials like lemongrass, red ginger, and yellow root. However, the main obstacles are limited product innovation, a lack of understanding of digital marketing, and production permit issues. These risks hinder the economic potential of the herbal sector if not addressed immediately. Therefore, this PKM aims to increase herbal product innovation, improve understanding and application of digital marketing, assist with the permitting process, and enhance the capacity of Human Resources (HR) for MSME (Micro, Small, and Medium Enterprises) herbal product entrepreneurs in Gayo Lues Regency. The community service was implemented in ABCD method with stages. Preparation: Students prepared the venue and coordinated with village officials and potential partners. Socialization: education on product benefits, innovation, business permits and product promotion. Training: Participants received training on registering for a Business Identification Number (NIB). Mentoring: The team provided guidance on designing promotional materials for social media and monitored and evaluated the promotions conducted by partners. The results of this PKM include three main aspects: Product Innovation: There was an improvement in product quality and variety. Digital Marketing: Partners' active social media accounts and marketplaces were optimized for sales. The partners successfully got their NIB. The project was a success, and the enthusiastic partners and village officials asked the team to return for another project on diversifying patchouli leaf products